Business Landscaping for Strategic Advantage: Evidence from a Multi-Sector Study - SUWARDY, Themin (Institutional Knowledge at Singapore Management University, 2014)
This paper sets out to make a significant contribution to research both by introducing a quantitative approach to landscaping the intensity of industry competition, and then demonstrating its applicability using cross-industry data. The underlying framework is Porter's Five Forces Model, which has wide acceptance in landscaping competitive intensity because of its simplicity, adaptability and flexibility, but is frequently hard to operationalise because it does not specify procedures for quantifying competitive factors. This paper presents a multivariate approach (i.e., the ICM framework) that enables the operationalisation of Porter's model in a quantitative manner, both at a firm and industry level. This framework is then applied to a total of 19 Australian industries. The results indicate that the degree of competition varies widely among Australian industries, characterized by high intensity of rivalry, low bargaining power of buyers, minimal bargaining power of suppliers, high threat of new entrants and wide-ranging threat of substitutes.